Enhancing SMEs Development Through Fintech: Insights from China's Economic Transformation - Hou Lijuan (International Journal of Education and Humanities, 2025)
Small and Medium-sized Enterprises (SMEs) are pivotal in driving domestic innovation and play a crucial role in China's economic transformation and industrial upgrading. Despite their importance, Chinese SMEs face persistent challenges, including constrained access to external funding, limited financing channels, and high borrowing costs, which hinder their development. Addressing these issues has become a critical concern in ensuring sustainable economic growth. In recent years, the rapid advancement of financial technology (fintech) has provided new opportunities to mitigate the financing constraints of SMEs. Emerging technologies such as blockchain, big data, and cloud computing have become integral components of fintech, fostering the continuous innovation of financial models. These advancements offer novel solutions to reduce financing costs, diversify funding sources, and improve SMEs' access to capital. This study systematically investigates the interplay between China's fintech innovation and SME development. It begins by assessing the current state of SMEs and fintech innovation, providing a comprehensive overview of their respective progress. Subsequently, the study evaluates the multifaceted impacts of fintech on SME operations, financing, and growth potential. Finally, the research identifies practical pathways to leverage fintech innovation in addressing SMEs' challenges, including policy recommendations and technological applications. The findings underscore the transformative potential of fintech in enhancing financial inclusivity and operational efficiency for SMEs. Policymakers and industry stakeholders are encouraged to promote fintech-driven solutions to foster a resilient and inclusive SME ecosystem, contributing to China’s broader economic modernization agenda